2009
DOI: 10.1002/ijc.24379
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of IDH1 codon 132 in glioblastomas and other common cancers

Abstract: Missense somatic mutations in IDH1 gene affecting codon 132 have recently been reported in glioblastoma multiforme (GBM) and other gliomas. The recurrent nature of the IDH1 mutations in the same amino acid strongly suggests that the mutations may play important roles in the pathogenesis of glial tumors. The aim of this study was to see whether the IDH1 codon 132 mutations occur in other human cancers besides glial tumors. We also attempted to confirm the occurrence of the IDH1 mutations in GBM of Korean patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
206
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(215 citation statements)
references
References 16 publications
7
206
1
1
Order By: Relevance
“…10,11 Lastly, immunopositivity may be useful in distinguishing diagnostically challenging diffuse gliomas from other tumor types, given that other primary central nervous system (CNS) tumors and metastatic malignancies are typically negative. 2,[12][13][14][15] The only other tumor type currently known to have a significant rate of IDH1 mutations is acute myelogenous leukemia. 16,17 Although the frequency of IDH1 mutation is well established in the most common forms of WHO grade II-IV gliomas, IDH1 mutant protein expression has not been widely examined in rare glioblastoma variants.…”
mentioning
confidence: 99%
“…10,11 Lastly, immunopositivity may be useful in distinguishing diagnostically challenging diffuse gliomas from other tumor types, given that other primary central nervous system (CNS) tumors and metastatic malignancies are typically negative. 2,[12][13][14][15] The only other tumor type currently known to have a significant rate of IDH1 mutations is acute myelogenous leukemia. 16,17 Although the frequency of IDH1 mutation is well established in the most common forms of WHO grade II-IV gliomas, IDH1 mutant protein expression has not been widely examined in rare glioblastoma variants.…”
mentioning
confidence: 99%
“…Deep sequencing further revealed that mutated IDH1 and IDH2 occur in a high proportion (>70%) of low‐grade (grade II–III) astrocytomas and oligodendrogliomas and secondary glioblastoma 51, 52, 88, 89. Since these initial reports, mutations in IDH1 and IDH2 have also been found in other diverse cancers including 16–17% of patients with AML,53 20% of patients with angioimmunoblastic T‐cell lymphomas,90 and more rarely in cholangiocarcinomas,91 breast carcinomas,92 acute lymphoblastic leukemias,93 prostate cancer,93 osteosarcoma,94 and others 53, 91, 92, 93, 95, 96, 97. Interestingly, and unlike IDH mutations in glioma which are almost entirely in IDH1 , AML have been shown to exhibit an approximately equal frequency of IDH1 and IDH2 mutations 53, 54…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%
“…It appears that the removal of the arginine, rather than the substitution of a specific residue, is the critical feature of this mutation, although the most frequent replacement observed is a histidine residue (R132H) 51, 52, 93, 98. Mutations in IDH2 in gliomas occur at a much lower frequency (0–6%) than IDH1 88 in the paralogous amino acid residue—R140—but also at R172.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%
“…A number of methods have been developed to detect IDH1 mutations including DNA sequencing (4,17), PCR-restriction fragment length polymorphism (RFLP) (18,19), PCR-single strand conformation polymorphism (SSCP) (20), pyrosequencing (21,22), and high-resolution melting curve analysis (HRM) (23,24). All of these methods have limitations in terms of sensitivity, ease of use and throughput.…”
Section: Comparison Of Immunohistochemistry Dna Sequencing and Allelmentioning
confidence: 99%